Assessment of quality of care of diabetic patients by health-care professionals in a city – A community-based cross-sectional study - Rajendra Tulank Ankushe; Mohan Kodiba Doibale; Purushottam Kumar (Asian Journal of Medical Sciences, 2023)
Background: Diabetes is undoubtedly one of the most challenging health problems of the 21st century. Patients from poor parts of the Indian urban population do not frequently have access to these health benefits despite having access to reliable screening methods and antidiabetic drugs. Hence, this study was designed to assess the quality of care of diabetic patients by health-care professionals in a city. Aims and Objectives: This study aims to assess the quality of care of diabetic patients by health-care professionals in a city. Materials and Methods: A community-based cross-sectional study was conducted in the city of Aurangabad, Maharashtra. The sample size calculated was 145 and we used the probability proportionate to size sampling technique to identify the number of participants. Results: Overall 9% of patients had good quality of care. Almost 61.4% were dissatisfied with their treating physician. Almost all patients going to public health centers complained of the unavailability of medications whereas three-fourth (73.5%) of patients complained of unavailability of investigations. Only 23.4% of diabetic patients were referred to a specialist for screening or management of complications. Conclusion: Quality of care assessed through patient’s opinion showed that most diabetic patients were not well informed about comprehensive diabetic management by the health-care providers. Glycemic controls in diabetic patients were far below recommended standards.